Ultrasonic Processing and Its Impact on the Rheology and Physical Stability of Flaxseed Fiber Dispersions - Maria-Carmen Alfaro-Rodríguez; Maria-Carmen Garcia-González; José Muñoz (Applied Sciences)
Ultrasonic homogenization is an emerging technique with significant potential to modify the structure and functionality of food ingredients. This study evaluated the effect of ultrasonic homogenization on the rheological behavior and physical stability of aqueous dispersions of flaxseed fiber. Flax mucilage, with health-promoting and techno-functional properties, is of growing interest in several industries. The samples were subjected to different ultrasonic treatments, varying in amplitude (from 40 to 100%) and duration (from 2 to 20 min), with and without preliminary rotor–stator homogenization. The rheological properties were analyzed using small-amplitude oscillatory shear (SAOS) tests and steady shear flow curves. Physical stability was assessed by multiple light scattering. The results revealed that short treatment under ultrasonic homogenization had minimal impact on the viscoelastic parameters and viscosity, regardless of the amplitude used. However, longer treatments significantly reduced both values by at least one order of magnitude or more, indicating the occurrence of microstructural degradation. The relevance of this research lies in its direct applicability to the development of functional foods, since it is concluded that control of the ultrasonic homogenization process conditions must be carefully selected to retain the desirable rheological properties and physical stability.